How reproducible are methods to measure the dynamic viscoelastic properties of poroelastic media?. (18th August 2018) - Bonfiglio, Paolo; Pompoli, Francesco; Horoshenkov, Kirill V.; Rahim, Mahmud Iskandar B.Seth A.; Jaouen, Luc; Rodenas, Julia; Bécot, François-Xavier; Gourdon, Emmanuel; Jaeger, Dirk; Kursch, Volker; Tarello, Maurizio; Roozen, Nicolaas Bernardus; et al.
Abstract: There is a considerable number of research publications on the acoustical properties of porous media with an elastic frame. A simple search through the Web of Science™ (last accessed 21 March 2018) suggests that there are at least 819 publications which deal with the acoustics of poroelastic media. A majority of these researches require accurate knowledge of the elastic properties over a broad frequency range. However, the accuracy of the measurement of the dynamic elastic properties of poroelastic media has been a contentious issue. The novelty of this paper is that it studies the reproducibility of some popular experimental methods which are used routinely to measure the key elastic properties such as the dynamic Young's modulus, loss factor and Poisson ratio of poroelastic media. In this paper, fourteen independent sets of laboratory measurements were performed on specimens of the same porous materials. The results from these measurements suggest that the reproducibility of this type of experimental method is poor. This work can be helpful to suggest improvements which can be developed to harmonize the way the elastic properties of poroelastic media are measured worldwide.